Verloren negatively regulates the expression of IMD pathway dependent antimicrobial peptides in Drosophila - Prakash, Pragya (Sci Rep, 2021)
Drosophila immune deficiency (IMD) pathway is similar to the human tumor necrosis factor receptor (TNFR) signaling pathway and is preferentially activated by Gram-negative bacterial infection. Recent studies highlighted the importance of IMD pathway regulation as it is tightly controlled by numbers of negative regulators at multiple levels. Here, we report a new negative regulator of the IMD pathway, Verloren (Velo). Silencing of Velo led to constitutive expression of the IMD pathway dependent antimicrobial peptides (AMPs), and Escherichia coli stimulation further enhanced the AMP expression. Epistatic analysis indicated that Velo knock-down mediated AMP upregulation is dependent on the canonical members of the IMD pathway. The immune fluorescent study using overexpression constructs revealed that Velo resides both in the nucleus and cytoplasm, but the majority (~ 75%) is localized in the nucleus. We also observed from in vivo analysis that Velo knock-down flies exhibit significant upregulation of the AMP expression and reduced bacterial load. Survival experiments showed that Velo knock-down flies have a short lifespan and are susceptible to the infection of pathogenic Gram-negative bacteria, P. aeruginosa. Taken together, these data suggest that Velo is an additional new negative regulator of the IMD pathway, possibly acting in both the nucleus and cytoplasm.